Tseng methods with inertial for solving inclusion problems and application to image deblurring and image recovery problems. Issue 3 (15th March 2020) - Padcharoen, Anantachai; Kitkuan, Duangkamon; Kumam, Wiyada; Kumam, Poom
Abstract : In this article, we offer two modifications of the modified forward‐backward splitting method based on inertial Tseng method and viscosity method for inclusion problems in real Hilbert spaces. Under standard assumptions, such as Lipschitz continuity and monotonicity (also maximal monotonicity), we establish weak and strong convergence of the proposed algorithms. We give the numerical experiments to show the efficiency and advantage of the proposed methods and we also used our proposed algorithm for solving the image deblurring and image recovery problems. Our result extends some related works in the literature and the primary experiments might also suggest their potential applicability.